A solution-processable wholly-aromatic bipolar host material for highly efficient blue electroluminescent devices. Issue 2 (17th December 2020) - Yuan, Jie; Jiang, He; Yang, Qingqing; Xiang, Yuan; Zhang, Ying; Dai, Yizhong; Li, Ping; Zheng, Chao; Xie, Guohua; Chen, Runfeng
Abstract : Highly efficient blue electroluminescent devices were realized by using a solution-processable wholly-aromatic bipolar host material prepared through an insulating C(sp 3 ) bridge linking strategy. Abstract : High-performance solution-processable host materials, especially for blue emitters, are greatly desired to develop low-cost and low-energy-consumption phosphorescent and thermally activated delayed fluorescent (TADF) organic light-emitting diodes (OLEDs). Here, we designed a wholly-aromatic bipolar host of 9, 9-bis(9-phenyl-9 H -carbazol-3-yl)-9 H -thioxanthene 10, 10-dioxide based on an insulating C(sp 3 ) bridge linked thioxanthone through a facile Friedel–Crafts-type substitution reaction with a total yield of 63%. The π-conjugate-interrupted linkage not only grants excellent thermal stability and good film-forming ability but also maintains the triplet energy at a high level of 3.05 eV. Therefore, two state-of-the-art solution processed blue phosphorescent and TADF OLEDs were achieved, showing that the turn-on voltages are about 5.0 V while the maximum external quantum efficiencies (EQEs) are of 20.5% and 11.2%, respectively. These performances are among the best results of the solution-processed blue OLEDs reported to date, paving the way for the straightforward construction of solution-processable hosts of blue OLEDs through the novel C(sp 3 ) bridge design strategy.